Understanding transmission pathways and integrated digital surveillance potential of antimicrobial resistance in Ethiopia in a One Health approach: a mixed-method study protocol - Muhammad Asaduzzaman; Christoph Gradmann; Andrea Sylvia Winkler; Zeleke Mekonnen; Ernst Kristian Rodland (BMJ Open)
Introduction Antimicrobial resistance (AMR) has a critical global impact, mostly affecting low- and middle-income countries. A major knowledge gap exists in understanding the transmission pathway of the gut colonisation with AMR bacteria between healthy humans and their animals in addition to the presence of those AMR bacteria in the surrounding environment. A One Health (OH) approach is necessary to address this multisectoral problem.Methods and analysis This cross-sectional, mixed-method OH study design will use both quantitative and qualitative methods of data collection. Quantitative methods will be carried out to assess the prevalence and risk factors associated with multidrug resistant Gram-negative bacteria and vancomycin-resistant enterococci in humans, animals (cattle) and the environment. The focus will be on cattle rearing as an exposure risk for AMR among humans. The assessment of AMR in the population of Jimma, Ethiopia with or without exposure to cattle will reinforce the importance of OH research to identify the impending exchange of resistance profile between humans and animals as well as its ultimate dissemination in the surrounding environment.The targeted semistructured key stakeholder interviews will aid to strengthen the OH-AMR surveillance in Ethiopia by understanding the acceptability of an integrated AMR surveillance platform based on the District Health Information Software-2 and the feasibility of its context-specific establishment.Ethics and dissemination The study has been approved by the Regional Ethics Committee, Norway, and the Institutional Review Board of Jimma University, Ethiopia. The study’s data will be stored on a secure server known as Services for Sensitive Data hosted by the University of Oslo. In addition, the new European Union Global Data Protection Guidelines for data sharing, storage and protection will be followed. We will publish the results in peer-reviewed journals and present the findings at national and international conferences.